2017
DOI: 10.6004/jnccn.2017.0104
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of Chest CT in Patients With Stage I and II Breast Cancer: An Opportunity to Increase Guidelines Compliance at an NCCN Member Institution

Abstract: The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) recommend that patients with clinical stage I/II breast cancer undergo advanced imaging for staging only when symptomatic. Regardless, many asymptomatic patients undergo chest CT. The goal of this study was to assess the use and results of chest CT in these patients at an NCCN Member Institution. Patients with breast cancer diagnosed between 1998 and 2012 were identified in a prospectively maintained database. All patients with clinical stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In another study, 43% required additional imaging, and in common with our study, a chest CT was the most common additional scan requested 9 . Regarding CT thorax findings, a study in keeping with ours found that stage I and II breast cancer patients required on average 2.34 additional scans to exclude metastases following a staging chest CT, with just 1.3% subsequently being diagnosed with pulmonary metastases 10 . In conclusion, in patients with T1‐3 breast cancer and clinically negative lymph nodes we report a very low rate of metastases at not inconsiderable financial cost.…”
Section: Stage % Metastatic Phenotype (Number Of Patients) Tn Her2 + supporting
confidence: 87%
“…In another study, 43% required additional imaging, and in common with our study, a chest CT was the most common additional scan requested 9 . Regarding CT thorax findings, a study in keeping with ours found that stage I and II breast cancer patients required on average 2.34 additional scans to exclude metastases following a staging chest CT, with just 1.3% subsequently being diagnosed with pulmonary metastases 10 . In conclusion, in patients with T1‐3 breast cancer and clinically negative lymph nodes we report a very low rate of metastases at not inconsiderable financial cost.…”
Section: Stage % Metastatic Phenotype (Number Of Patients) Tn Her2 + supporting
confidence: 87%
“…The incidence of distant metastasis in patients with early breast cancer has been reported to be low [3,7,8,11]. Furthermore, there was no added survival value of additional staging studies [24].…”
Section: Discussionmentioning
confidence: 99%
“…After bone, the lung is the second most common distant metastatic site in patients with breast cancer, followed by the brain and liver [6]. However, the prevalence of radiologicallyevident distant lung metastasis in early stage breast cancer is low, approximately 0.2% and 1.2% for stage I and II disease, respectively [3,[7][8][9][10][11]. Most of the existing guidelines, including the National Comprehensive Cancer Network (NCCN), European Society for Medical Oncology (ESMO), and American Society of Clinical Oncology (ASCO), recommend staging chest-CT only for advanced disease [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest CT is an imaging modality widely used in breast cancer patients to evaluate pulmonary symptoms or cancer spread. Regardless of the cancer stage, many clinical institutions currently perform chest CT in patients with breast cancer as a baseline and follow-up imaging modality [ 7 ]. More recently, feasibility studies have supported that CT measurement of vertebral attenuation during abdomen or chest CT performed for other indications can be used for opportunistic osteoporosis screening or evaluation of bone density loss [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%